COMPARISON OF SIMPLE ADITIVE WEIGHTING MEHOD WITH MULTI-OBJECTIVE OPTIMIZATION BY RATIO ANALYSIS: SAW and MOORA DSS - Panggabean, Erwin; Sianturi, Fricles Ariwisanto; Selvia, Sindu; Dewi, Sumitra (Politeknik Ganesha Medan, 2023)
Abstract: One of the advantages of the MOORA method is its high flexibility and good selectivity. This is because MOORA is able to determine the goals of conflicting criteria, where the criteria can be profitable or unfavorable. While the advantage of the SAW method is that it can determine the weight value of each attribute, then proceed with a ranking process that will select the best alternative from a number of alternatives and the assessment will be more precise because it is based on the predetermined criteria and preference weights. Some of the weaknesses of the SAW method include, the data entered must be correct and precise, so as not to cause errors during the weighting and ranking of criteria, while the drawback of this MOORA method is that there must be a weight that is calculated to continue the calculation of the data which is then calculated on each criterion and range of criteria. This is what prompted the researchers to explore the research entitled